2021
DOI: 10.1186/s12864-021-07694-z
|View full text |Cite
|
Sign up to set email alerts
|

Genomic selection and genetic gain for nut yield in an Australian macadamia breeding population

Abstract: Background Improving yield prediction and selection efficiency is critical for tree breeding. This is vital for macadamia trees with the time from crossing to production of new cultivars being almost a quarter of a century. Genomic selection (GS) is a useful tool in plant breeding, particularly with perennial trees, contributing to an increased rate of genetic gain and reducing the length of the breeding cycle. We investigated the potential of using GS methods to increase genetic gain and accel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…However, estimates of th realised prediction accuracy in this study are unlikely to be upwardly biased by spurious correlations between unlinked markers and QTLs induced by historical selection history (sensu Yu et al, 2006;Toosi et al, 2010;Guo et al, 2014) as the breeding population was confounded with trial, and prediction accuracy was estimated for each trial-bygenomic environment. However, studies (Windhausen et al, 2012;Hickey et al, 2014;Werner et al, 2020) demonstrated that the realised prediction accuracy is driven by parental genetic values for training populations with strong family structures, such as in this and other horticultural tree crop studies (Kumar et al, 2012;O'Connor et al, 2021). While not undertaken here, training models within families (e.g., Biscarini et al, 2017) might avoid bias arising from strong family structure (Hickey et al, 2014;Werner et al, 2020), but such training might be expensive with little utility due to poor prediction accuracy in unrelated families (Riedelsheimer et al, 2013;Schopp et al, 2017).…”
Section: Discussion Of Study Resultsmentioning
confidence: 94%
“…However, estimates of th realised prediction accuracy in this study are unlikely to be upwardly biased by spurious correlations between unlinked markers and QTLs induced by historical selection history (sensu Yu et al, 2006;Toosi et al, 2010;Guo et al, 2014) as the breeding population was confounded with trial, and prediction accuracy was estimated for each trial-bygenomic environment. However, studies (Windhausen et al, 2012;Hickey et al, 2014;Werner et al, 2020) demonstrated that the realised prediction accuracy is driven by parental genetic values for training populations with strong family structures, such as in this and other horticultural tree crop studies (Kumar et al, 2012;O'Connor et al, 2021). While not undertaken here, training models within families (e.g., Biscarini et al, 2017) might avoid bias arising from strong family structure (Hickey et al, 2014;Werner et al, 2020), but such training might be expensive with little utility due to poor prediction accuracy in unrelated families (Riedelsheimer et al, 2013;Schopp et al, 2017).…”
Section: Discussion Of Study Resultsmentioning
confidence: 94%
“…Alternatively, given genomic-based heritability estimates for STC were moderate, there may be evidence for many markers of small effect. As such, it may be worth investigating the use of genomicselection for stick-tight traits, as previously demonstrated for yield in macadamia [55].…”
Section: Discussionmentioning
confidence: 96%
“…The application of different methods depends on the conditions of the research in question, for example, when there is less kinship between the breeding and training population, the Bayesian method is preferred to GBLUP, and on the other hand, for traits having high heritability and traits that are controlled by a moderate number of genes, it is better to use the Bayesian A and B method, respectively [ 92 ]. Since GEBVs can be estimated in seedlings, the GS approach can play an essential role in increasing genetic gain per time unit and reducing the breeding period in forest trees [ 94 ].…”
Section: Experimental Approaches To Characterizing Disease Resistance...mentioning
confidence: 99%
“…In a recent study on the nut yield of Macadamia integrifolia Maiden and Betche, moderate and high prediction accuracy was obtained for yield and yield stability traits, respectively. The results of this study showed that GS can reduce the selection cycle for yield by seven years (from 21 to 14 years) and double the genetic gain for this trait [ 94 ]. Some reports showed the predictive accuracy of traits related to the growth and quality of wood in trees such as fire tree, Pinus pinaster Ait.…”
Section: Experimental Approaches To Characterizing Disease Resistance...mentioning
confidence: 99%
See 1 more Smart Citation